Konsep ukhuwah dalam perspektif al-Qur’an dan relevansinya dalam kehidupan bermasyarakat: (Kajian Surat Al-Hujurat Ayat 10) - Moh Faesal (Al Irfani: Journal of Al Qur'anic and Tafsir, 2022)
Abstract - Ukhuwwah is a fabric of brotherhood among human beings that transcends ethnic, racial, religious, tribal, hereditary, social background and so on. In the Qur'an there are many kinds of ukhuwah, this is shown because of the many words akh in the Qur'an, such as ukhuwah ubudiyah, ukhuwah insaniyah, ukhuwah diniyah and ukhuwah wathaniyah. In life in this world, a Muslim can understand the existence of views and even opinions that are different from his religious views, because all of this cannot be outside of God's will. In Surat al-Hujurrat verse 10 it is very clear, Allah says that Muslims are brothers, and orders to carry out corrective relations if there is a misunderstanding between groups of Muslims. So the Qur'an provides examples and causes of rifts in relations while at the same time prohibiting every Muslim from making a fuss. Therefore, brotherhood must be built and grown in our daily lives. In interacting with the community, we place great emphasis on ukhuwah so that we can live peacefully side by side with each other without any gaps.